Validation of the Chinese version of the low physical activity questionnaire (LoPAQ) with ActiGraph accelerometer in hemodialysis patients - Rui, Huang (BMC Nephrol, 2021)
BACKGROUND: Valid instruments for measuring physical activity at the low end of the physical activity range and producing quantitative results are required among dialysis patients who are extremely inactive. This study aimed to translate and adapt a Chinese version of the low physical activity questionnaire (LoPAQ) and to examine its reliability and validity among hemodialysis patients. METHODS: This was a cross-sectional study. The LoPAQ was translated into Chinese and culturally adapted following the standardized questionnaire adaptation process. Participants wore an ActiGraph for seven consecutive days and were asked to complete the Chinese version of the LoPAQ (C-LoPAQ) following the ActiGraph monitoring period. The criterion validity of the C-LoPAQ was examined with accelerometers using Spearman’s correlation coefficients. Bland-Altman plots were adopted to determine the absolute agreement between methods. The test-retest reliability was analyzed using the intraclass correlation coefficient (ICC). RESULTS: Eighty-five hemodialysis patients had valid accelerometers and C-LoPAQ data. The total walking time reported on LoPAQ was correlated with step counts by ActiGraph (rho = 0.47, p < 0.01). A moderate correlation was also observed between the C-LoPAQ and the ActiGraph-measured physical activity for total calories (rho = 0.44, p < 0.01). There was a fair correlation between ActiGraph-measured sedentary time and C-LoPAQ-measured inactive time (rho = 0.22, p < 0.05). The test-retest reliability coefficients of C-LoPAQ ranged from 0.30 to 0.66. CONCLUSIONS: The C-LoPAQ demonstrated moderate validity for measuring low levels of physical activity, especially walking, and total kilocalories of physical activity among hemodialysis patients in China. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12882-021-02230-3.